Analysis of Combinatorial Problems in the Python Programming Language - Alimova Rayhon Abdug'aforovna; O`rolova Munira Ahmad qizi (Genius Publishing Group, 2023)
This article describes combinatorics and its combinations, and a program in the python programming language that displays the result.
Keywords: combinatorics; combinatorics problems; basic combinations; ordered set